PROMOSI PENGEMBANGAN KREATIVITAS PESERTA DIDIK DALAM PEMBELAJARAN - Tekeng, St. Nurjannah Yunus (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
Every individual has the potential to be creative. Creativity is more than the use of someone’s imagination. This is a lifestyle, personality characteristic, and ways of understanding the world.Creativity depends on two main factors namely here-dity (nature) and the influence of environment (nurture). To support the develop-ment of this students’ creative potential, there is a need for an instructional design that facilitate the active participation of students in explorating their potential, trying out, examining, hypothesizing, and finding out a new creative idea. Be-sides, instructors should develop openness and respecting students thinking. Do-ing this is a way to respond tothedemand of the era.